Countering violent extremism in Indonesia : priorities, practice and the role of civil society - Sumpter, Cameron (2020)
Indonesia has experimented with initiatives aimed at countering violent extremism (CVE) since the wave of arrests following the first Bali bombing attack in 2002. Initial efforts involved police attempting to develop relationships of trust with terrorists in custody. Today, a broader range of strategies are employed, from promoting peace among youth and thwarting the allure of extremist narratives, to managing prisoners and assisting former terrorists reintegrate with society. The lead government body since 2010 has been the national counterterrorism agency, Badan Nasional Penanggulangan Terorisme (BNPT), which is tasked with coordinating stakeholders in Indonesia’s struggle with domestic terrorism. But managing the divergent and sometimes competing interests of Indonesia’s large state institutions has not been straightforward, and effective collaboration between relevant state agencies remains an obstacle to the success of CVE initiatives. Where government has fallen short, civil society organisations (CSOs) often fill the gaps, and a number of dedicated practitioners now have invaluable experience, local contacts, and the specific knowledge required for countering extremism in the Indonesian context. CSOs also possess greater levels of trust among the communities they engage than security-centric state agencies could possibly hope to achieve. Yet instead of exploiting these civil society resources, the BNPT has largely preferred an independent (and top-down) approach to CVE initiatives, collaborating if and when assistance is required. The Indonesian government should make better use of the unique legitimacy and expertise of civil society organisations.